Distribution of major toxins in Rhinella marina parotoid macroglands using Desorption-Electrospray-Ionization mass spectrometry imaging (DESI-MSI). (June 2020) - Mailho-Fontana, Pedro L.; Porcari, Andreia M.; Eberlin, Marcos N.; Jared, Carlos; Antoniazzi, Marta Maria; Pimenta, Daniel C.; Sciani, Juliana M.
Abstract: Amphibian cutaneous glands secrete toxins used in different vital functions including passive defense. Through Desorption Electrospray Ionization-Imaging we analyzed the distribution of the major toxins of the toad Rhinella marina parotoid macroglands. Alkaloids and steroids showed characteristic distribution and intensity within the glands and were also present at lower levels on the skin surface. A comprehensive overview of toxins distribution in toads' skin might help to understand their full biological role within the amphibians. Graphical abstract: Image 1 Highlights: Amphibians possess granular glands associated to chemical defense. Actual tissue distribution of toads' toxins remains unknown. We have pinpointed some toad toxins in the parotoid macroglands. Alkaloids are distributed throughout the gland; whereas steroids are peripheral. Toxins are stored within the macrogland, presenting large concentration variation.